Indeks ekonomi hijau di Kabupaten Kerinci Provinsi Jambi - Zikri, Afdhol (e-Jurnal Ekonomi Sumberdaya dan Lingkungan, 2025)
The purpose of the research is to understand the development of the green economy index indicators in Kerinci Regency, Jambi Province. To know the green economy index from selected indicators in Kerinci Regency, Jambi Province.The purpose of the research is to understand the development of indicators for the green economy index in Kerinci District, Jambi Province.Implementation of green economy as a sustainable development effort that is able to balance economic growth, environmental conservation, and social welfare. This study aims to determine the development of green economy index indicators in Kerinci Regency, Jambi Province. The method used is a quantitative approach with secondary data in the form of time series data for 2014–2023 obtained from various regional and national government agencies. The analysis was carried out using a composite index method that combines selected indicators from the three pillars. The results of the study show that Kerinci Regency is in the moderate category in implementing a green economy, with index values that tend to increase every year. The social pillar provides the highest contribution to the index, followed by the environmental and economic pillars. However, there are still challenges in optimizing the use of renewable energy, land management, and increasing the productivity of the environmentally friendly economic sector. This study recommends increasing community capacity, strengthening local policies, and utilizing local potential in a sustainable manner to encourage an increase in the green economy index in the future.